Caribbean Report 05-03-1999 - The British Broadcasting Corporation; Greaves, Keith Stone (correspondent); Ramphal, Shridath (interviewee); Richards, Ken (correspondent); Anthony, Kenny (interviewee); Richardson, Wakefield (correspondent); Clarke, Oscar (interviewee); Luncheon, Roger (interviewee); Thomas, Bert (interviewee); Andrew Thomas, Kimberly (correspondent) (The British Broadcasting Corporation, 1999)
1. Headlines with anchor Keith Stone Greaves (00:23) 2. High level talks on the US European Union dispute continue in London with the US Secretary of State Madeline Albright scheduled to meet with UK Foreign Secretary Robin Cooke. The World Trade Organization will hold an emergency meeting to discuss the current impasse. CARICOM negotiator Shridath Ramphal condemns US actions. Ken Richards reports on the ongoing consultations on US retaliatory tariffs (00:24 – 02:52) 3. Prime Minister of Saint Lucia Kenny Anthony will meet with government officials to discuss the ongoing banana trade war between the US and European Union and will continue to lobby for a Caribbean banana regime. Saint Lucia is a major producer of bananas to the EU (02:53 – 5:44) 4. Wakefield Richardson reports on polling results in Anguilla national elections. The Anguilla National Alliance captured three seats, Anguilla United Party and Anguilla Democratic Party each picked up two seats. The former coalition government led by Chief Minister Hubert Hughes will form the next government in Anguilla (05:45 - 6:58) 5. A Commonwealth Observer Group arrives in Antigua ahead of the general election. The Group’s mandate is to meet with political parties, election officials, independent candidates and all interest groups and report its findings to the Commonwealth Secretary General. Keith Stone Greaves reports (06:59 – 08:16) 6. In Guyana, stores remained closed after crowds attacked police and started a fire, riot police used tear gas to disperse a crowd attending a political meeting organised by the opposition People National Congress (PNC). PNC General Secretary Oscar Clarke comments on the incident as an act of disruption and an attempt to injure PNC leader Desmond Hoyte. Head of the Presidential Secretariat Roger Luncheon called on Hoyte to decrease inflammatory comments. Colin Smith reports from Guyana. (08: 17 – 10:21) 7. Increasing political tension in Haiti and recent murders draw condemnation from the UN Security Council. The Council ...